Quality Evaluation of Academic Thesis Abstracts Based on ANSI / NISO Z39.14 (R2015) Standard: A Case Study - Maryam Karimi; Maryam Kazerani; Maryam Shekofteh; Hassan Jahanihashemi (International Journal of Information Science and Management, 2019)
Abstracts are regarded as valuable tools in assessing the relevance of documents during information retrieval. The determination of abstract compliance based on international standards is one of the methods which can be used for generating qualified information, reducing costs and establishing aligned coordination with international standards. Further, ANSI/NISO Z39.14 standard is one of the international standards presented by NISO committee which its final amendment was published in March 2015 and proposed some principles in terms of content and structural elements of different sources like theses. For this purpose, the present study aimed to evaluate the abstracts of Persian theses in different educational levels with ANSI/NISO Z39.14 standard at Shahid Beheshti University of Medical Sciences (SBMU) during 2010-2014. 386 Persian abstracts were selected from among the abstracts in master’s theses, PhD dissertations, Medical Doctorate(MD) and specialized medicine theses at different schools. The standard texts of ANSI/NISO Z39.14 (R2015) were used as the instrument including 15 structural and 5 content elements. Results indicated that there was a significant difference between the consistency of structural and content elements of the standards among the abstracts of the selected theses at different educational levels in different schools. The results suggest that an instructional and a coherent model should be developed, based on international and latest edition standards such as ANSI/NISOZ39.14 guideline for abstracts which are necessary to be followed by all centers in order to improve the style of writing abstracts.